Mitochondrial genetic diversity of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) associated with cassava in Lao PDR - Leiva, Anne; Chittarath, Khonesavanh; López Alvarez, Diana; Vongphachanh, Pinkham; Gómez Jiménez, Maria Isabel; Sengsay, Somkhit; Wang, Xiao-Wei; Rodríguez, Rafael; Newby, Jonathan Craig; Cuéllar, Wilmer Jose (MDPI, 2022)
Cassava Mosaic Disease (CMD) caused by Sri Lankan cassava mosaic virus (SLCMV), has rapidly spread in Southeast Asia (SEA) since 2016. Recently it has been documented in Lao PDR. Previous reports have identified whitefly species of B. tabaci as potential vectors of CMD in SEA, but their occurrence and distribution in cassava fields is not well known. We conducted a countrywide survey in Lao PDR for adult whiteflies in cassava fields, and determined the abundance and genetic diversity of the B. tabaci species complex using mitochondrial cytochrome oxidase I (mtCOI) sequencing. In order to expedite the process, PCR amplifications were performed directly on whitefly adults without DNA extraction, and mtCOI sequences obtained using nanopore portable-sequencing technology. Low whitefly abundances and two cryptic species of the B. tabaci complex, Asia II 1 and Asia II 6, were identified. This is the first work on abundance and genetic identification of whiteflies associated with cassava in Lao PDR. This study indicates currently only a secondary role for Asia II in spreading CMD or as a pest. Routine monitoring and transmission studies on Asia II 6 should be carried out to establish its potential role as a vector of SLCMV in this region.